A extensão universitária como instrumento de efetivação dos direitos humanos fundamentais no curso de direito - Carvalho, André Azeredo (2008)
The developed research intended to demonstrate the possibilities of using university extension in a way to promote the humanization of the law teaching, as well as to discuss the need of modifying the approach of the human rights issue at the juridical academies and to make their social responsibility worthy. Trough the historical gathering of the juridical teaching in Brazil, it was possible to conclude that since the days of the Brazilian Empire until the actual days, this teaching is dominated by the technical and non critic ideology imposed by the occidental capitalism. This form of teaching development shocks with the conceptions of knowledge used as power, liberty dialogue, symbolic power and multiculturalism defended by authors as Michel Foucault, Paulo Freire, Pierre Bourdieu, Boaventura de Sousa Santos, producing a different optic when analyzing the actual academic activities and its effects on the law students formation. This way, emerges the problem about the possibilities of the humanization of the formation of these students using the university extension by the equilibrated dialogue between scientific and traditional knowledge’s. The dialectic methodology was used by the analysis between the theory described by the legislation and the reality that has been practiced on the juridical teaching.